Bond strength to etched and Re-etched enamel, dentin and dentino-enamel junction (Mustansiria Dental Journal, 2018)
Etching and re-etching are frequently done technique to alter the tooth surface andmakes it more receptive to adhesion. This study was done to assess the effect of reetchingtechnique on bond strength to enamel, dentin and dentino-enamel junction.60 extracted human upper premolars teeth were collected cleaned, sectioned at thelevel of cervical line, embedded in acrylic block exposing certain grounded flatsurface of the crown and divided into 2 groups:Group A (30 etched specimens) etched with total etch (37% phosphoric acid)for 15 sec.Group B (30 re-etched specimens) etched and re-etched with total etch(37% phosphoric acid).Both groups were subdivided into:Subgroup 1 10 enamel specimensSubgroup 2 10 dentin specimensSubgroup 3 10 dentino-enamel junction specimensA standardized cylinders of light cure composite resin were bonded, and thespecimens were stored in deionized distilled water for 24 h. and testing was done withzwick test machine and statistically analyzed using analysis of variance test(ANOVA) and student t-test.The results showed non significant difference between all subgroups in groupA(etching group) and between all subgroups in group A Vs. group B subgroup 2(reetchedE), and showed a significant difference between all subgroups in group A Vsgroup B subgroup 3 (re- etched EDJ) and between group B sub1&2 (re-etched E & D)Vs group B sub 3 ( re-etched DEJ) ,furthermore there were a highly significantdifferences between all subgroups in group A Vs group B sub 2(re-etched D) andbetween group B sub 2(re-etched E) Vs groupB sub 2(re-etched D).Re-etching the enamel didn’t decrease the shear bond while re-etching dentinmarkedly decreased the bond strength. Further more re-etching the dentino-enameljunction lies in between.